Implementasi Association Rule Untuk Rekomendasi Strategi Up-Selling dan Cross-Selling Produk Menggunakan FP-Growth - Nabiilah, Nabiilah; M. Afdal; Novita, Rice; Mustakim (AI Society & STMIK Indonesia, 2024)
BC 4 HNI Pekanbaru is a subsidiary of PT. HNI-HPAI Indonesia offers a diverse range of items for sale. Insufficiently effective promotions, despite high transaction volumes, can result in certain items being less recognized and thus impractical. The purpose of employing the FP-Growth algorithm in data mining is to uncover product association patterns and produce rules for sales tactics using the CRM approach. Implementing CRM strategies that incorporate cross-selling and up-selling techniques can enhance sales. Cross-selling involves offering additional products or services connected to the items purchased, while up-selling involves encouraging customers to buy higher-value goods than initially intended, boosting sales of more expensive items. Among the 20 results obtained from analyzing transaction data from July 2023 to December 2023 using FP-Growth, only the rules with a minimum support value of 5% and a minimum confidence of 70% are considered for cross-selling strategies. Additionally, the rules with a minimum support value of 5% and a minimum confidence of 10% are considered for up-selling.